A REVISION OF THE NEW WORLD MOTH GENUS ATHYRMA HÜBNER (LEPIDOPTERA: EREBIDAE) - Adams, Morton S.; Mccabe, Timothy L. (Zootaxa, 2022)
The genus Athyrma Hübner, [1823] 1816 is revised, with a generic re-description and transcriptions of original descriptions (with translations) of all described species provided. Sixteen Athyrma species are recognized in this paper. Nine species are new: A. brigittae Adams & McCabe sp. nov., A. tapichensis Adams & McCabe, sp. nov., A. urbanae Adams & McCabe, sp. nov., A. yasuni Adams & McCabe, sp. nov., A. ciboney McCabe & Adams, sp. nov., A. cryani McCabe & Adams, sp. nov., A. itatiaia McCabe & Adams, sp. nov., A. romacki McCabe & Adams, sp. nov., and A. svensoni McCabe & Adams, sp. nov. Taxonomic changes are as follows: Athyrma antica Schaus, 1912, syn. nov., a junior synonym of A. nodosa; A. cunesema Hampson, 1926, syn. nov., a junior synonym of A. cunesema; “Athyrma” cordigera Walker, 1869, comb. nov., syn. nov., a junior synonym of Celiptera levina Stoll, 1781. A lectotype is designated for A. adjutrix (Cramer, 1780). Neotypes are designated for four species: Athyrma nodosa Möschler, 1880, A. orbana Möschler, 1880, A. tuberosa (Felder and Rogenhofer, 1874), and A. ganglio Hübner, [1831] 1825. Athyrma ganglio Hübner, [1831] 1825, rest. stat. and A. dormitrix Guenée in Boisduval and Guenée, 1852, rest. stat. are removed from synonymy and restored as valid species. Athyrma has been associated with the Eulepidotinae however is here tentatively assigned to Erebinae: Poaphilini because of its similarity to Mimophisma Hampson, 1926. Illustrations of male and female adult habitus, ultimate instar larva, dissections of male and female external and internal genitalia are provided. Athyrma misera Butler, 1879 is removed from Athyrma and placed in Ezra gen. nov. Nymbis resecta Dognin, 1912 is removed from its current placement in Athyrma and placed in Facies gen. nov. Checklists of all three genera are provided.